2011
DOI: 10.1007/s00417-011-1786-6
|View full text |Cite
|
Sign up to set email alerts
|

GDF-15: a novel serum marker for metastases in uveal melanoma patients

Abstract: Our data suggest that GDF-15 can be used as a serum marker for the diagnosis of metastases in UM patients. Further data collection and analysis are necessary to evaluate a possible prognostic role of GDF-15 in predicting early metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
(35 reference statements)
2
27
0
Order By: Relevance
“…Elevated serum levels of MIA, S100-β, and osteopontin (OPN) correlated with liver UM metastases, and the combination of these three biomarkers enhanced the sensitivity and specificity in detecting hepatic metastases [324]. Serum levels of cytokeratin 18 (TPS) [325], insulin-like growth factor 1 (IGF1) [326], growth differentiation factor 15 (GDF15) [327], and Parkinson protein N7 (PARK7 or DJ-1) [328] are significantly more elevated in metastatic than in metastasis-free patients. An increase in VEGF on serial measurements might indicate the presence of metastases, but its value was limited by the large variability among patients [329].…”
Section: Biomarkersmentioning
confidence: 99%
“…Elevated serum levels of MIA, S100-β, and osteopontin (OPN) correlated with liver UM metastases, and the combination of these three biomarkers enhanced the sensitivity and specificity in detecting hepatic metastases [324]. Serum levels of cytokeratin 18 (TPS) [325], insulin-like growth factor 1 (IGF1) [326], growth differentiation factor 15 (GDF15) [327], and Parkinson protein N7 (PARK7 or DJ-1) [328] are significantly more elevated in metastatic than in metastasis-free patients. An increase in VEGF on serial measurements might indicate the presence of metastases, but its value was limited by the large variability among patients [329].…”
Section: Biomarkersmentioning
confidence: 99%
“…15 was identified many years ago, the principal function, specific receptor, and signaling pathways of GDF-15 remained uncertain [13]. Increased GDF-15 expression is a common feature of many cancers [14][15][16][17] and serum GDF-15 levels are frequently elevated in metastatic tumors, often in parallel with the stages and extent of disease [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In UM, a number of proteins have already been examined in patient sera including OPN [48], MIA [49], S100ß [50], GDF15 [51], PARK7 [52], ME20 [53], soluble c-Met [54] and IGF [55], each demonstrating varying degrees of sensitivity and specificity in the identification of patients with disseminated disease compared with metastasis-free UM patients and/or normal healthy controls. Of these proteins OPN, MIA, GDF15, PARK7 and ME20 were detected in the current study; however, only MIA and GDF15 demonstrated significantly higher levels in the secretome of UM compared with NCM, with no significant difference between the levels detected in HR- and LR-UM.…”
Section: Discussionmentioning
confidence: 99%